Impact of simultaneous exposure to RF and gradient electromagnetic fields on implant MR safety labeling - Zanovello, Umberto; Arduino, Alessandro; Fuss, Carina; Goren, Tolga; Zilberti, Luca; Bottauscio, Oriano (Magnetic resonance in medicine, 2026)
Purpose To investigate whether heating contributions produced by radiofrequency (RF) and gradient fields superpose sufficiently at the worst‐case locations to justify their simultaneous consideration in magnetic resonance imaging (MRI) implant safety labeling. Theory and Methods Six implant models were positioned in an ASTM phantom and realistically implanted in two anatomical human models, and exposed to gradient and RF fields at 64 MHz and 128 MHz. The simulations with the anatomical body models considered different axial exposure landmarks inside the RF and gradient body coils. The exposures were scaled to represent two sets of scenarios: either limited by the implant's MR conditional labeling to a fixed peak temperature rise, or representing an EPI or TrueFISP examination with clinically relevant parameters, where the implant label is not limiting. Results The temperature enhancement due to the combined RF and gradient sources, evaluated with respect to the maximum values obtained separately, depends on the implant, pulse sequence, and exposure landmark. A maximum relative enhancement of about 65% was found in the ASTM phantom, and maximum absolute enhancements above 0.3 K were found in anatomical models with realistic pulse sequences. Conclusion There are clinically relevant MR examination scenarios where the maximum heating contributions produced by RF and gradient fields combine, enhancing the local peak temperature increase beyond that obtained from either assessment alone. The results prove to be useful for defining safety margins on the maximum allowable temperature increase, avoiding the requirement of a combined gradient coil and RF test.